1984
DOI: 10.1111/j.1471-0528.1984.tb05894.x
|View full text |Cite
|
Sign up to set email alerts
|

Male twins at birth and 18 years later

Abstract: summary An 18‐year follow‐up examination on 56 male twins born in 1962–1963 was done by comparing birth records with the results of medical examinations at drafting for military service in 1981 Of the studied twins, 14.3% were unfit for military service compared with 6.2% of the total population of Norwegian conscripts in the same year. Preterm delivery rather than twinning per se is suggested as an explanation for this result. Vision was impaired in the preterm twins more often than in the total group of cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…Consistent ®ndings are reported from a questionnaire survey of 474 Belgian twin pairs born in 1950 which reported lower marital and fertility rates among male (especially monozygotic) twins (Steeno & Vlietinck, 1989) although not apparently related to prematurity. Similar suggestions that male twins may be less well developed physically are reported from surveys of Norwegian military conscripts in which male twins were more than twice as likely to be un®t, mainly due to long-term sequelae of prematurity (Nilsen et al, 1984). The only twin study of testicular function reported to date identi®ed that familial factors account for a large proportion of the variability in blood levels of gonadotrophins (LH, FSH), sex steroids (total and free testosterone, oestradiol) and their metabolites (dihydrotestosterone, 3aandrostanediol glucuronide) and that genetic factors accounted for 25±76% of the variability of gonadotrophins and sex steroids (Meikle et al, 1987).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Consistent ®ndings are reported from a questionnaire survey of 474 Belgian twin pairs born in 1950 which reported lower marital and fertility rates among male (especially monozygotic) twins (Steeno & Vlietinck, 1989) although not apparently related to prematurity. Similar suggestions that male twins may be less well developed physically are reported from surveys of Norwegian military conscripts in which male twins were more than twice as likely to be un®t, mainly due to long-term sequelae of prematurity (Nilsen et al, 1984). The only twin study of testicular function reported to date identi®ed that familial factors account for a large proportion of the variability in blood levels of gonadotrophins (LH, FSH), sex steroids (total and free testosterone, oestradiol) and their metabolites (dihydrotestosterone, 3aandrostanediol glucuronide) and that genetic factors accounted for 25±76% of the variability of gonadotrophins and sex steroids (Meikle et al, 1987).…”
Section: Discussionsupporting
confidence: 75%
“…One caveat is that twins may not be representative of singletons. Perinatal effects of twin gestation including prematurity and gestational complications are more frequent among twins and may explain the lowered physical ®tness, fertility and longevity of twins compared with singleton siblings (Wyshak & White, 1969;Wyshak, 1978;Nilsen et al, 1984;Steeno & Vlietinck, 1989). As the perinatal period is critical for testicular development, such biological consequences of twinhood mean that factors identi®ed from twin studies should be veri®ed by sibling or other studies where possible.…”
Section: Discussionmentioning
confidence: 99%
“…twins and non-twins (Rutter & Redshaw, 1991). In general population adult samples, twins probably have a slight reduction in intelligence (Record et al 1970), although this has not been found in all studies (Nilsen et al 1984).…”
mentioning
confidence: 77%
“…Most studies that have found differences between singletons and twins have examined young twins. A host of studies comparing older twins with singletons have failed to find differences in physical characteristics and cognitive abilities, 6 suggesting that any differences between twins and singletons are ‘washed out’ by five years of age. In addition, most studies have not matched twins with singletons in terms of genetic background nor early environmental experiences.…”
Section: Are Twins the Same As Singletons?mentioning
confidence: 99%